Word-of-mouth and brand equity: the study on mediating role of brand trust at public higher learning institutions / Norhafiza Mazlan - Mazlan, Norhafiza (2017)
The usage of tablet PC's from the multiple brands is not a new phenomenon to the consumers. However, the marketers always find a new strategy in order to strengthen their own brands in the market place. It is because; every each of strategy that was used by marketers will affect consumers during buying decision process. Besides, the buying decision process among consumers also affected by another factor such as recommendation or in another words known as informal conversation between a consumer to another consumers about a product that had been used before. Therefore, the main objective of this study is to examine the relationship between Word-of- Mouth (WOM) with brand equity and the mediating role of brand trust. Using hierarchical multiple regression analysis and Process Procedure for SPSS by Preacher and Hayes (2008), the result show that the two dimensions of Word-of-Mouth namely Word-of-Mouth Praise (WOMP) and Word-of-Mouth Activity (WOMA) have a significant relationship with the brand equity dimensions (brand loyalty, brand awareness and perceived quality) mediated by brand trust. A total 500 final year undergraduate students (full time and part time) across the three higher learning institutions in Kedah and Perlis were participated as respondents. Data for all the study variables have been collected through self-administered questionnaires. Thus the result of this study supports the objectives of this study. Overall, the results indicate that the framework provides a good understanding of the factors that influence brand equity.